2012
DOI: 10.3126/ijls.v5i1.5953
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Wetland Winter Migratory Avian Biodiversity in Hathnikund Barrage in Haryana State in India

Abstract: Hathnikund is a place in Yamunanagar District in Haryana where Yamuna Rivers forms a sort of Lake over raised plinth after descending into plains from Himalayas nearby Ponta Sahib town near Haryana-Himachal Border. At the same time, Tajewala Barrage is one more pool like scenic place where waters of Western Yamuna Canal are collected by Govt. of Haryana for subsequent multipurpose. In the present studies, wetland bird’s diversity of Hathnikund has been recorded, analyzed and interpreted. The studies were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, in village, namely, Kunjpura, where a very large pond of deep waters is available at a distance of 4-5 km from Yamuna in Karnal, Rudy Shelduck was seen in impressive manner. As such present study revealed that Rudy Shelduck has a penchant for river water and stays away from traditional rural ponds (Gupta and Kaushik, 2011) (Gupta et al, 2009;2010 a-b;Gupta and Kaushik, 2010a-e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in village, namely, Kunjpura, where a very large pond of deep waters is available at a distance of 4-5 km from Yamuna in Karnal, Rudy Shelduck was seen in impressive manner. As such present study revealed that Rudy Shelduck has a penchant for river water and stays away from traditional rural ponds (Gupta and Kaushik, 2011) (Gupta et al, 2009;2010 a-b;Gupta and Kaushik, 2010a-e).…”
Section: Resultsmentioning
confidence: 99%
“…It is evident from figure 4 that out of 60 species of wetland birds observed from Asan Barrage, 31 species of wetland birds were winter migratory and 9 species of birds were Local Migratory. It is crucial to mention that Gupta and Kaushik (2011) reported 47 species of wetland birds from Hathinikund Barrage in Yamunanagar district in Haryana. Also, Tak et al (2010) observed 31 species of wetland birds from the Hathinikund Barrage in Yamunanagar district in Haryana.…”
Section: Resultsmentioning
confidence: 99%
“…These awesome journeys are performed by Arctic Terns Sterna paradisaea, ter visiting wetland birds in rural village ponds [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Associated studies on varied aspects of field ornithology have also been done in Haryana [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, Damdamma Saras resort was built by Haryana Tourism department. It is pertinent to mention that wetland birds in Haryana have been studied by Gupta and Kaushik [1][2][3][4][5][6][7][8]; Gupta et al [9][10][11] and Gupta et al (12)(13)(14)(15)(16). No one has focused attention on avian biodiversity of Damdamma Jheel in India and hence the present studies.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, White-necked Stork, Oriental White Ibis and Painted Storks were observed rarely. Regular winter migratory birds seen in winter include Asian Open-bill Stork Anastomus oscitans, Eurasian Spoonbill Platalea leucorodia, Northern Shoveller Anas clypeata, Northern Pintail Anas acuta, Common Teal Anas crecca, Common Pochard Aythya ferina, Gadwall Anas strepera, Spot-billed Duck Anas poecilorhyncha, Spotted Redshank Tringa erythropus, Common Redshank Tringa totanus, Common Greenshank Tringa nebularia, Kentish Plover Charadrius alexandrinus, White-tailed Lapwing Vanellus leucurus, Marsh Sandpiper Tringa stagnatilis, Wood Sandpiper Tringa glareola, Common Sandpiper Actitis hypoleucos, White Wagtail Motacilla alba and Yellow Wagtail Motacilla flava.It is interesting to note that Red-crested Pochard, Tufted Pochard, Mallard, Garganey, Pallas's Gull and Black-headed Gull sighted elsewhere in Northern Haryana[8][9] are seldom sighted in Damdamma Lake in winter season in southern Haryana. Little Egrets, Pond Herons, Egrets, Black winged Stilts, Red-wattled Lapwing (in plenty) are seen regularly.…”
mentioning
confidence: 99%